-2K+2/k+1 怎么转换成(4/k+1)-2
1个回答
(-2K+2) / (k+1)
=(-2k-2+4) / (k+1)
=[-2(k+1) +4] / (k+1)
= -2 + 4 / (k+1)
=4/(k+1) - 2
o(∩_∩)o
相关问题
怎么算2[√(4k^4+7k^2+3)]/(k^2+1) =2√[(4k^2++3)/(k^2+1)]
(1/2)×|-2-(3/k)|×|2k+3|=4怎么解成:(2k+3)²=8|k|的
计算 -1/4(2k³+4k²-28)+1/2(k³-2k²+4k)
-k^2/2k^2+1=-1/2+1/4k^2+2 怎么得出来的
4(K+1)^2-1怎么算得到(2K+1)(2K+3)?
(1/3)k(4k^2-1)+(2k+1)^2为什么=(1/3)(k+1)[4(k+1)^2-1]
把参数方程x=4k/1-k^2,y=4k^2/1-k^2化成普通方程
|2k-1|=2√(k²+1),k怎么解
-1/4(2k^3+4k5^2-28)+1/2(k^3-3k^2+4k)
数列证明.由a2k-1,a2k,a2k+1成等差数列,及a2k,a2k+1,a2k+2成等比数列,得2a2k=a2k-1